2019
DOI: 10.1159/000495308
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of the Retinal Effects of Hydroxychloroquine Treatment in Healthy Eyes

Abstract: Purpose: To evaluate the influence of hydroxychloroquine in visual field and retinal layer thickness. Methods: This is a retrospective cross-sectional study. Patients taking hydroxychloroquine without signs of hydroxychloroquine retinopathy were included. Optical coherence tomography segmentation was used to obtain the ETDRS map thickness of each retinal layer. Groups were divided into short-term (< 5 years) and long-term (≥5 years) drug use. Results: We included 93 eyes of 93 patients (short-term: 25 eyes; lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…This was accompanied by a concomitant decrease in the IRL and, more specifically, the GCL. These findings are in agreement with other studies [6, 12, 14, 16-18]. However, some others deny this possibility [13, 19].…”
Section: Discussion/conclusionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was accompanied by a concomitant decrease in the IRL and, more specifically, the GCL. These findings are in agreement with other studies [6, 12, 14, 16-18]. However, some others deny this possibility [13, 19].…”
Section: Discussion/conclusionsupporting
confidence: 93%
“…In each sector, the full retina (FR), inner retina (IRL) (from the inner limiting membrane to the external limiting membrane), outer retina (ORL) (from the external limiting membrane to the RPE), ganglion cell (GCL), and inner nuclear (INL) layer thicknesses were evaluated. The mean of the thicknesses found in the 4 sectors of each concentric ring was also determined [5, 12-14].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, several previous studies have found that long-term HCQ treatment caused progressive thinning of the retinal nerve fiber layer. 37,38 In agreement with previous studies, we hypothesize that the alterations in retinal VD were more pronounced than the neural structural or at least affected first before seeing any changes in neural structural. Although some researchers found that FAZ area was enlarged in SLE patients, 13,14 we did not detect the changes of FAZ size, which may indicate FAZ area is not a candidate biomarker for detecting early stage of LR in SLE patients.…”
Section: Discussionsupporting
confidence: 91%
“…The parafoveal inferior area showed significant retinal thinning at 3 months and 6 months after hydroxychloroquine usage (Table 4) which corresponded to the typical pattern of this toxicity and coincided with a recent large study of patients using hydroxychloroquine for less than 5 years duration. 24 However, two studies had documented that the typical parafoveal distribution of toxicity is not common in Asians, who show a pericentral pattern of foveal thinning. 25,26 But this perifoveal pattern in the first study was observed in Korean patients while the second study although include East Asian, Southeast Asian, and Filipinos, the total percentage of Asian was only 18%.…”
Section: Discussionmentioning
confidence: 99%